1996
DOI: 10.1897/1551-5028(1996)015<1357:eoiveo>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in Vitro Exposure of Beluga Whale Splenocytes and Thymocytes to Heavy Metals

Abstract: Abstract-The effects of in vitro exposure of beluga whale splenocytes and thymocytes to different concentrations of mercury chloride (HgCl 2 ), cadmium chloride (CdCl 2 ), and lead chloride (PbCl 2 ) were evaluated. The cells were cultured for 66 h with either concanavalin A (Con-A), phytohemagglutinin-P, or without mitogen, after which percentage of cell death and proliferation were evaluated. Increased percentage of cell death was observed in Con-A-stimulated thymocytes cultured with HgCl 2 , while the viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…Phagocytosis and lymphoblast transformation in gray seal pups are adversely affected in vitro by mercury (Lalancette et al 2003). Effects of heavy metals on beluga whale splenocytes and thymocytes in vitro indicate functional impairment (De Guise et al 1996). A sex‐dependent effect of zinc on phagocytic activity of seal blood leukocytes was found (Pillet et al 2000).…”
Section: Melisa Cell Proliferation To Negative and Positive Controls mentioning
confidence: 99%
“…Phagocytosis and lymphoblast transformation in gray seal pups are adversely affected in vitro by mercury (Lalancette et al 2003). Effects of heavy metals on beluga whale splenocytes and thymocytes in vitro indicate functional impairment (De Guise et al 1996). A sex‐dependent effect of zinc on phagocytic activity of seal blood leukocytes was found (Pillet et al 2000).…”
Section: Melisa Cell Proliferation To Negative and Positive Controls mentioning
confidence: 99%
“…To date, few studies have directly examined thyroid disruption in marine mammals. PCBs and their hydroxylated metabolites have been identified in tissues [229][230][231][232][233][234][235]237,[248][249][250][251][252], and these compounds specifically alter thyroid homeostasis in other mammals [112,113,246,247]. Thyroid gland abnormalities have been detected in harbor seals from the contaminated North Sea, but a causative link to contaminants has not been established [253].…”
Section: Mammalsmentioning
confidence: 99%
“…Specifically, in cetaceans, metal exposure has been correlated with infectious disease mortality, parasitic infections and pneumonias and histopathological changes in lung and kidney tissues [7][8][9]. Cetacean cell culture studies showed that metals can induce cytotoxic, immunotoxic and genotoxic effects [10][11][12][13][14][15][16][17]. Thus, animal and tissue culture studies suggest that metals could be a health concern to cetaceans.…”
Section: Introductionmentioning
confidence: 99%